Problem konstytucyjności instytucji przepadku w świetle nowelizacji Kodeksu karnego z dnia 7 lipca 2022 r. - Paszta, Michał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2024)
The author undertook to discuss the issues related to changes regarding the amendment of the Penal Code – Article 44b, which extends the institution of forfeiture with new regulations. The introduction of new regulations into force currently raises many questions and a number of doubts regarding confiscation and its compliance with the constitution. Although the subject matter is relatively new in nature, from the perspective of doctrine, clear positions have already begun to form, which the author presents and analyzes. The examples collected during the research, the analyzed views and insight into the regulations - both those currently in force and outdated ones, allow us to formulate a hypothesis that may constitute an excellent starting point for considerations regarding the foundations of forfeiture and the future of this institution.
Keywords: forfeiture; confiscation; constitution; amendment; penal code